Parasite Load and STRs Genotyping of Toxoplasma gondii Isolates From Mediterranean Mussels (Mytilus galloprovincialis) in Southern Italy - Santoro, Mario; Viscardi, Maurizio; Boccia, Federica; Borriello, Giorgia; Lucibelli, Maria Gabriella; Auriemma, Clementina; Anastasio, Aniello; Veneziano, Vincenzo; Galiero, Giorgio; Baldi, Loredana; Fusco, Giovanna (Frontiers in Microbiology, 2020)
Toxoplasmosis is a zoonotic food-borne disease caused by Toxoplasma gondii, a land-derived protozoan parasite that infects a broad range of terrestrial and aquatic hosts. T. gondii may reach coastal waters via contaminated freshwater runoff and its oocysts may enter into the marine food web. Marine invertebrates as mussels being filter feeders are exposed and may concentrate T. gondii oocysts representing a potential source of infection for animals and humans. The present works investigated the prevalence, parasite burden and genotypes of T. gondii in the Mediterranean mussels (Mytilus galloprovincialis) from southern Italy. We sampled a total of 382 individual Mediterranean mussels from May to August 2018 from seven production sites in the Gulf of Naples (Campania region). An additional sample including 27 farmed Mediterranean mussels was obtained in February 2018 from a mollusk depuration plant in Corigliano Calabro (Calabria region). T. gondii DNA was detected in 43 out of 409 (10.5%) Mediterranean mussels from seven out of eight sampling sites. The number of T. gondii copies/g in the digestive gland ranged from 0.14 to 1.18. Fragment analysis of Short Tandem Repeats (STRs) at 5 microsatellite loci was performed from 10 T. gondii PCR positive samples revealing the presence of five distinct genotypes including one corresponding to type I and four atypical genotypes. These findings suggest potential implications of epidemiological importance for human and animal health because both type I and atypical genotypes could be highly pathogenic.